2017
DOI: 10.1016/j.apgeog.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating climate justice: Green infrastructure and suburban disadvantage in Australia

Abstract: are grateful to conference participants for their useful comments and feedback. They greatly acknowledge the assistance of the City of Gold Coast Council in funding survey printing and mailing, but note that the views reported here do not necessarily reflect the perspective of the City of Gold Coast Council. The authors are grateful to survey respondents for their participation, to Event Cinemas for providing movie ticket incentives for survey participation, and they appreciate the helpful comments of the anon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 44 publications
0
16
1
2
Order By: Relevance
“…In contrast with a study that indicated that different socio-economic conditions do not affect perceptions of green measures [88], other papers show evidence for such a correlation. For example, Sheng et al [110] found that household income and the amount of government subsidy received for owned pasture area correlated with the positive support of a restoration project.…”
Section: Socio-economic and Location-specific Conditionscontrasting
confidence: 70%
“…In contrast with a study that indicated that different socio-economic conditions do not affect perceptions of green measures [88], other papers show evidence for such a correlation. For example, Sheng et al [110] found that household income and the amount of government subsidy received for owned pasture area correlated with the positive support of a restoration project.…”
Section: Socio-economic and Location-specific Conditionscontrasting
confidence: 70%
“…Of the articles that report on groundwork adaptation actions, the most common focus is on documenting stakeholder perspectives on climate change and their attitudes towards adaptation (35%, n = 135). Some of these articles seek to understand stakeholders' views on climate change, risk and adaptation [25], while others explore mechanisms to more effectively engage community members in climate change adaptation planning and implementation [26]. Other studies aim to understand how adaptation is influenced by stakeholder perspectives on climate change, current socio-economic situations, attitudes towards change, and engagement in decision-making [27].…”
Section: Adaptation Initiatives Primarily Focus On Groundwork Adaptatmentioning
confidence: 99%
“…suggesting that promoting support for green infrastructure in disadvantaged neighborhoods should be accompanied with efforts to address inequality (Ambrey et al, 2017). suggesting that, "initial green roof plant composition and roof microclimate may have long-term effects on community dynamics, ecosystem function, and urban biodiversity" (Aloisio et al, 2017).…”
Section: Climate Change and Resiliencementioning
confidence: 99%